2009
DOI: 10.1007/s10548-009-0131-4
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Removal of Eye-Movement and Blink Artifacts from EEG Signals

Abstract: Frequent occurrence of electrooculography (EOG) artifacts leads to serious problems in interpreting and analyzing the electroencephalogram (EEG). In this paper, a robust method is presented to automatically eliminate eye-movement and eye-blink artifacts from EEG signals. Independent Component Analysis (ICA) is used to decompose EEG signals into independent components. Moreover, the features of topographies and power spectral densities of those components are extracted to identify eye-movement artifact componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 26 publications
(33 reference statements)
1
44
0
Order By: Relevance
“…Equation (10) can be obtained through the EVD on the covariance matrix C x of e x, where e x denotes the random column vector of X.…”
Section: Preprocessingmentioning
confidence: 99%
See 2 more Smart Citations
“…Equation (10) can be obtained through the EVD on the covariance matrix C x of e x, where e x denotes the random column vector of X.…”
Section: Preprocessingmentioning
confidence: 99%
“…The EEG signals are the electrical potential recordings captured from the scalp sensors, where the electrical potentials mean that the components of the brain activity [3] are mixed. In addition, the EEG signals may be contaminated by the artifacts of eye activity or muscular activity [4][5][6][7][8][9][10]. Therefore, analyzing EEG signals becomes a challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to obtain reliable results, automatic response detection and data classification for plant electrical signals were to be implemented. Many studies reported artifacts detection methods for EEG and EKG analysis [16]- [20]. These methods were appropriate for human biological signals and offline analysis.…”
Section: Ozone Critical Level Detectionmentioning
confidence: 99%
“…Afterwards, this classifier automatically identifies eye-artefact-independent components [9,13]. Another type of technique for effectively reducing ocular artefacts is the regression-based method [14,15]. Good reference EOG channels are used and the regression coefficients that describe the transmission from these EOG channels to EEG channels are calculated.…”
Section: Introductionmentioning
confidence: 99%